Acute toxicity of mercury to freshwater cultured milkfish Chanos chanos: Clinical symptoms and lethal concentration assessment - Ezraneti, Riri; Khalil, Munawar; Affandi, Ridwan; Nirmala, Kukuh (Journal of Marine Studies, 2024)
The increasing use of mercury in the industrial sector poses significant risks to freshwater ecosystems and aquatic organisms. Milkfish (Chanos chanos), a widely consumed species, is now being reared in freshwater environments, raising concerns about mercury bioaccumulation and food safety. This study aimed to determine the median lethal mercury concentration for milkfish at 96 hours (LC50) in freshwater using an experimental approach and probit analysis. Five mercury concentrations were tested: 0 (control), 0 .110 mg Hg/L, 0.195 mg Hg/L, 0.347 mg Hg/L, and 0.618 mg Hg/L. The results indicated that mercury is highly toxic to milkfish, with a 96-hour LC50 of 0.147 mg Hg/L. Clinical symptoms observed included loss of reflex movements, irregular swimming, frequent surfacing with widened mouth and operculum openings, convulsions, and ventilation of the ram before mortality. These findings highlight the acute toxicity of mercury in freshwater milkfish and underscore the potential health risks associated with mercury contamination in aquaculture systems.